PUBLIC PARTICIPATION DALAM PEMBENTUKAN LAYANAN PENGELOLAAN SAMPAH DI KOTA BANDA ACEH - Ana Zahara; Rudi Kurniawan; Junaidi Junaidi; Saiful Bahri (Universitas Bina Taruna Gorontalo, 2023)
This study aims to address public participation in dealing with several environmental and other public issues in Aceh. One in every one of them is the excessive quantity of waste generated within the vicinity and the waste control system, which is predicated on traditional exercises which include open dumping. This observation proposes enhancing the contemporary waste management method based on the lively participation of residents and favoring neighborhood groups in handling their waste. The case have a look at is the city of Banda Aceh, that's positioned in the capital town of Aceh Province. The survey consequences had been evaluated based totally on quantitative and qualitative techniques, including descriptive statistical strategies, thematic analysis, and SWOT evaluation. The outcomes display that residents' employment fame is correlated with their pride in city control services. The Pearson correlation coefficient shows an immediate relationship between citizen participation and the fine for municipal solid waste control services. extra than fifty eight% of the respondents said that network participation in sorting waste at its supply changed into well below exceptional. despite the fact that extra than 98% of respondents have shown a superb mindset towards energetic participation in segregating waste from its assets at the same time as producing lower amounts of waste. The modified waste management process pattern includes three stages: waste that has been disposed of, its transportation, and final disposal. In addition, residents' active participation in the waste management process is of great concern. The proposed pattern can serve as a roadmap for local city managers to facilitate public participation in Banda Aceh City and other cities with similar socio-economic profiles.